Double‐layer modified silica with potential reinforcement for solution polymerized styrene‐butadiene rubber/butadiene rubber composite. Issue 16 (22nd November 2021) - Tian, Qingfeng; Tang, Yuan; Lv, Xiaohui; Niu, Liyong; Wang, Yanpeng; Ding, Tao; Li, Xiaohong; Zhang, Zhijun
Abstract: Silica was dual layer surface‐capped by hexamethyldisilamide (HMDS) and epoxy‐terminated ethylene‐vinyl acetate copolymer (EVA) via an in situ synthesis route to acquire greatly improved compatibility and interfacial interactions with solution polymerized styrene‐butadiene rubber/butadiene rubber (SSBR/BR). The as‐prepared HMDS/EVA‐SiO2 was used to reinforce SSBR/BR matrix so as to improve the wet skid resistance and wear resistance, and reduce the rolling resistance of the rubber–matrix composite. Besides, the as‐fabricated HMDS/EVA‐SiO2 was characterized by Fourier transform infrared spectrometry and transmission electron microscopy; and the tensile strength and tear resistance of the HMDS/EVA–SiO2 /SSBR/BR composites were measured with a universal testing machine. Moreover, an Akron abrasion test was performed to determine the abrasion volume of SiO2 –SSBR/BR composites; and a rotary rheometer was run to evaluate the dynamic mechanical properties of the vulcanized rubber‐matrix composites. Findings indicate that the EVA resin latex synthesized by emulsion polymerization can effectively improve the compatibility and forms a permeability layer between the rubber and nano‐silica of the composites. The as‐fabricated HMDS/EVA‐SiO2 ‐SSBR/BR composite exhibits greatly improved wear resistance and wet skid resistance as well as significantly reduced rolling resistance, showing potential as green tire tread material with increased security and service life as well as reduced energy consumption. Abstract :